Silent no more: sexual violence in conflict as a challenge to the worldwide church - D. Tombs (Acta Theologica)
The Tearfund report Silent No More (2011) challenges the worldwide church to respond to sexual violence in conflicts. This article argues that a church response should have pastoral, biblical and theological dimensions. Starting with the Silent No More report it examines the prevalence of sexual violence in conflict and the silence of the churches on this subject. Building on feminist readings of sexual violence in biblical narratives it then explores sexual violence referenced in the death of Saul (I Samuel 31) alongside news reports of the death of Muammar Gaddafi in October 2011. It also suggests that sexual violence is a key to understanding the scandal of the cross and the death of Jesus of Nazareth. It concludes that if biblical scholars and theologians give more attention to sexual violence within the bible they can offer positive help towards a more constructive response to sexual violence by the churches.